2007
DOI: 10.1083/jcb.200701122
|View full text |Cite
|
Sign up to set email alerts
|

Tripin/hSgo2 recruits MCAK to the inner centromere to correct defective kinetochore attachments

Abstract: hSgo2 (previously annotated as Tripin) was recently reported to be a new inner centromere protein that is essential for centromere cohesion (Kitajima et al., 2006). In this study, we show that hSgo2 exhibits a dynamic distribution pattern, and that its localization depends on the BUB1 and Aurora B kinases. hSgo2 is concentrated at the inner centromere of unattached kinetochores, but extends toward the kinetochores that are under tension. This localization pattern is reminiscent of MCAK, which is a microtubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
156
0
14

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(179 citation statements)
references
References 38 publications
9
156
0
14
Order By: Relevance
“…Our results show that Sgo is a protector of cohesin around centromeres in chromosomes assembled in these extracts, as we see a perfect correlation between increased distance between sister centromeres and decreased cohesin staining in the absence of Sgo or its targeting kinase Bub1. This is important because it corroborates the previously proposed role of Sgo as a protector of centromeric cohesin from the prophase dissociation pathway in a "clean" system (Xenopus extracts) without interference of the spindle assembly checkpoint in which Sgo also participates (Indjeian et al Huang et al 2007). In contrast, the role of Sgo as a protector of cohesin along chromosome arms, proposed for human cells, seems not to be relevant in this system (Nakajima et al 2007).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results show that Sgo is a protector of cohesin around centromeres in chromosomes assembled in these extracts, as we see a perfect correlation between increased distance between sister centromeres and decreased cohesin staining in the absence of Sgo or its targeting kinase Bub1. This is important because it corroborates the previously proposed role of Sgo as a protector of centromeric cohesin from the prophase dissociation pathway in a "clean" system (Xenopus extracts) without interference of the spindle assembly checkpoint in which Sgo also participates (Indjeian et al Huang et al 2007). In contrast, the role of Sgo as a protector of cohesin along chromosome arms, proposed for human cells, seems not to be relevant in this system (Nakajima et al 2007).…”
Section: Discussionsupporting
confidence: 86%
“…In Saccharomyces cerevisiae, an organism in which there is no prophase release of cohesin, Sgo1 is not required for cohesion but for sensing tension between sister chromatids (Indjeian et al 2005). Human Sgo2 also acts as a sensor of tension (Huang et al 2007;Lee et al 2008), whereas a number of studies in HeLa cells show that knock down of Sgo1 by small interfering RNA (siRNA) leads to premature separation of the sister chromatids and prometaphase arrest McGuinness et al 2005). Therefore, in these transformed human cells, Sgo1 appears to protect a small population of cohesin both at arms and at centromeres from the prophase pathway (Nakajima et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in mammalian cells Sgo2 also seems to promote MCAK localization at the centromere and cells depleted of Sgo2 exhibit erroneous kinetochore-microtubule attachments and high rates of chromosome mis-segregation in anaphase. 68 The idea that Sgo2 might contribute to correction of kinetochore mis-attachments by promoting INCENP localization at the centromere is particularly interesting in light of another recent study suggesting that INCENP might actually function as the 'sensor' of the system. 71 Sandall and coworkers found that, in budding yeast, the Survivin/INCENP protein complex is responsible for mediating the linkage between centromeres and microtubules in an in vitro approach that makes use of the sequence-specific budding yeast centromere.…”
Section: How Does Aurora B Detect Kinetochore-microtubule Mis-attachmmentioning
confidence: 99%
“…Sgo2 localizes at the inner centromere of mammalian chromosomes and its local distribution changes as chromosomes become bi-oriented and develop tension across the centromere. 67,68 Studies in fission yeast have also shown that Sgo2 interacts with and promotes the centromeric localization of INCENP/ Survivin. 69,70 It is less clear if the centromeric localization of Aurora kinase is also regulated by Sgo2, although it could do so indirectly via INCENP.…”
Section: How Does Aurora B Detect Kinetochore-microtubule Mis-attachmmentioning
confidence: 99%
“…Antigen-affinity purified antibodies against hSMC1, SA-1, and hRAD21 were described previously (Gregson et al, 2001(Gregson et al, , 2002. Mouse monoclonal antibody (mAb) specific for CENP-E and rabbit polycloncal antibody specific for Tripin/hSgo2 were published previously (Yen et al, 1991;Huang et al, 2007). Polyclonal antibodies against Aurora A (rabbit; Novus Biologicals, Littleton, CO) and SA2 (goat; Bethyl Laboratories, Montgomery, TX) as well as mouse monoclonal antibodies specific for NuMA (Calbiochem, San Diego, CA), Polo-like kinase 1 (Plk1) (Abcam, Cambridge, MA), SUV39H1 (Millipore, Billerica, MA), CENP-A (Abcam), and ␣-tubulin, ␤-tubulin, and ␥-tubulin (Sigma-Aldrich) were used.…”
mentioning
confidence: 99%